Terminological discussion in modern psychology on the phenomenon of "digital Generation Z" - Maria I. Ryzhkova; Lidia S. Rychkova (Russian Journal of Education and Psychology)
Background. In the mid-20th century, the widespread information technology revolution led to the appearance of numerous studies into the emerging phenomenon of "digital generation". The scientific literature presents many variations that define and name the subjects living in the described period of time in different ways. Different views on the definition of this generation among foreign and domestic scientists indicate the ambiguity of understanding and the complexity of this phenomenon.